2008
DOI: 10.1002/jbio.200810020
|View full text |Cite
|
Sign up to set email alerts
|

FTIR protein secondary structure analysis of human ascending aortic tissues

Abstract: Journal of BIOPHOTONICSThe advent of moderate dilatations in ascending aortas is often accompanied by structural modifications of the main components of the aortic tissue, elastin and collagen. In this study, we have undertaken an approach based on FTIR microscopy coupled to a curve-fitting procedure to analyze secondary structure modifications in these proteins in human normal and pathological aortic tissues. We found that the outcome of the aortic pathology is strongly influenced by these proteins, which are… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
30
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 51 publications
(31 citation statements)
references
References 31 publications
1
30
0
Order By: Relevance
“…3-B,D). This slight shift may be explained by the differences in secondary structures of collagen and elastin 29,31,57 . Collagen is composed mainly of α-helical structures, while elastin is primarily β-sheets; the amide I band of α-helical structures occurs between 1643–1667 cm −1 , and for β-sheet structures occurs between 1610–1645 cm −1 29,57 .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…3-B,D). This slight shift may be explained by the differences in secondary structures of collagen and elastin 29,31,57 . Collagen is composed mainly of α-helical structures, while elastin is primarily β-sheets; the amide I band of α-helical structures occurs between 1643–1667 cm −1 , and for β-sheet structures occurs between 1610–1645 cm −1 29,57 .…”
Section: Resultsmentioning
confidence: 99%
“…These investigators demonstrated that normal and aneurysmal human arterial tissue biopsies could be differentiated using the ratio of α-helical to β-sheet structures and principal component analysis (PCA) 29 , hierarchical cluster analysis (HCA) 30 and factorial discriminant analysis (FDA) 32 . Furthermore, curve-fitting was applied to the spectra to detect alteration of β structures in the protein spectral profile of pathological aortas 31 . Although this group of studies set the ground work for differentiation of aneurismal from healthy aortic tissues, there has been minimal confirmation with histology or biochemical analysis, and the relative degradation of the primary ECM components (elastin and collagen) associated with aneurysm condition has not been specifically evaluated.…”
Section: Introductionmentioning
confidence: 99%
“…FTIR provides information of secondary structures of proteins (Bonnier et al, 2008) and also is used for EOs analysis (Vera & Chane-Ming, 1999). Only the treatments under neutral pH are presented because different pH conditions had no effect on FTIR results.…”
Section: Ftir Spectrummentioning
confidence: 99%
“…Some distinct features can be observed between S4 peptides and S4 fibers on these global spectra; in peculiar the amide I band located at 1645 cm -1 in S4 peptides is narrower and shifted at 1627 cm -1 in S4 fibers. Since the amide I-II region consists of several bands strongly dependent on secondary conformations, it was subjected to curve fitting in order to resolve the various underlying and overlapping spectral features that contribute to this complex region [8][9][10][11]. The decomposed FTIR spectra of the amide I-II region are superimposed on global spectra in Figure 2 and the assignments of the vibrational bands are reported in Table1.…”
Section: Secondary Structuresmentioning
confidence: 99%